DETERMINAN PENGAMBILAN KEPUTUSAN DALAM PERENCANAAN PERSALINAN PADA KELAS IBU HAMIL - Fatimah Fatimah Fatimah; Sugeng Triyani; Aisyah Aisyah Aisyah (Jurnal Ilmu dan Teknologi Kesehatan, 2014)
Class of pregnant mother means a group of pregnant women those learn health of pregnancy through discussion and sharing experiences. The members improve their knowledge and skills related childbirth, postpartum care, newborn care, myths, infectious diseases and birth certificates. There are 117 pregnant women (about 25% from total class members) do not pass the pregnancy class, and about 42 mothers from each 366 mothers in total decide to deliver their baby with herbalist. This research aims to investigate the determinants of decision making among pregnant mother related to with whom they will deliver their futurebaby. The research design employed is study analytic where apply cross sectional approach. Sample is chosen among 117 pregnancy class members on period August to September 2013 at Puskesmas in Jatinegara district. The result show us that factor influence the decision made are variables related parity, education, knowledge, attitudes, frequency of visits and health personnel support. Therefore, most related variable is health support namely p value=0,000 and OR=25,267. Suggestion: increasing the number formation of a new pregnancy class in order to monitor pregnancy progress, immediate clinical decision when at risk, as well as husband involvement and participation to accompany pregnant mother at pregnancy class.